Application of liquid-phase microextraction to the analysis of plant and herbal samples - Diuzheva, Alina; Locatelli, Marcello; Tartaglia, Angela; Goga, Michal; Ferrone, Vincenzo; Carlucci, Giuseppe; Andruch, Vasil (Phytochemical analysis, 2020)
INTRODUCTION: The analysis of plant and herbal samples is a challenging task for analytical chemists due to the complexity of the matrix combined with the low concentration of analytes. In recent years different liquid-phase microextraction (LPME) techniques coupled with a variety of analytical equipment have been developed for the determination of both organic and inorganic analytes. OBJECTIVE: Over the past few years, the number of research papers in this field has shown a markedly growing tendency. Therefore, the purpose of this review paper is to summarise and critically evaluate research articles focused on the application of LPME techniques for the analysis of plant and herbal samples. RESULTS: Due to the complex nature of the samples, the direct application of LPME techniques to the analysis of plants has not often been done. LPME techniques as well as their modalities have been commonly applied in combination with other pretreatment techniques, including a solid-liquid extraction technique supported by mechanical agitation or auxiliary energies for plant analysis. Applications and the most important parameters are summarised in the tables. CONCLUSION: This review summarises the application of the LPME procedure and shows the major benefits of LPME, such as the low volume of solvents used, high enrichment factor, simplicity of operation and wide selection of applicable detection techniques. We can expect further development of microextraction analytical methods that focus on direct sample analysis with the application of green extraction solvents while fully automating procedures for the analysis of plant materials.
Keywords: Liquid Phase Microextraction; Plants; mikroextrakce kapalné fáze; rozpouštědla; Solvents; rostliny